Knowledge and systems sciences : 18th International Symposium, KSS 2017, Bangkok, Thailand, November 17-19, 2017, Proceedings /: 18th International Symposium, KSS 2017, Bangkok, Thailand, November 17-19, 2017, Proceedings. (2017) - Unknown
No abstract available